Discovery of potential dual-target prodrugs of HIV-1 reverse transcriptase and nucleocapsid protein 7. Issue 16 (15th August 2020) - Sun, Songkai; Huang, Boshi; Li, Zhuo; Wang, Zhao; Sun, Lin; Gao, Ping; Kang, Dongwei; Chen, Chin-Ho; Lee, Kuo-Hsiung; Daelemans, Dirk; De Clercq, Erik; Pannecouque, Christophe; et al.
Graphical abstract: Highlights: Dual-target prodrug of HIV-1 reverse transcriptase inhibitor and NCp7 inhibitor. Dual target prodrug modification improves antiviral activity and selectivity index. The compound releases parent drugs linearly in the plasma, with prodrug properties. Abstract: In the present work, we described the design, synthesis and biological evaluation of a novel series of potential dual-target prodrugs targeting the HIV-1 reverse transcriptase (RT) and nucleocapsid protein 7 (NCp7) simultaneously. Among them, the most effective compound 7c was found to inhibit HIV-1 wild-type (WT) strain at double-digit nanomolar concentration (EC50  = 42 nM) in MT-4 cells, and sub-micromole (EC50  = 0.308 μM) to inhibit HIV-1 NL4-3 strain in TZM-bl cells. This is a significant improvement over the parent drug MT. In addition, it showed moderate inhibitory potency (EC50  = 1.329 μM) against the HIV-1 K103N/Y181C double mutant strain (MT-4 cells). The metabolic stability in human plasma of compound 7c indicated that it can release the active forms of the parent drugs MT and AZT in a linear time-independent manner and turn out to be a potential prodrug.